2018
DOI: 10.1520/gtj20170098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Properties and Failure Modes of Heat-Treated Granite in Dynamic Splitting Test

Abstract: Dynamic Brazilian disc (or splitting) tests were carried out to study the characteristics of energy dissipation and failure behavior of heat-treated granite under impact loading. Six groups of granite samples were treated at the temperatures of 25°C, 100°C, 300°C, 500°C, 700°C, and 900°C, respectively. Each group of heat-treated samples was tested with three impact velocities of 5.4, 7.7 and 13.7 m/s in a modified split Hopkinson pressure bar. An average change rate of incident energy (ACRIE) was proposed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Considering that the rock surrounding wellbores was affected by drilling vibration, thermal impact and earthquake waves and that tensile failure frequently occurred in the wellbore, dynamic Brazilian disc splitting tests were carried out. The cumulative damage of the rock increased exponentially with increasing strain rate, the ultimate failure modes of the disc rock samples were closely related to the impact velocity, and the dynamic tensile strengths measured by the test were far larger than the static tensile strengths [ 21 – 24 ]. Analysing the above studies, it was found that high temperature, high in situ stress and dynamic disturbances were taken into account, but the influence of the cross section of high-depth wellbores, medium water and cycle heat recovery times was overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the rock surrounding wellbores was affected by drilling vibration, thermal impact and earthquake waves and that tensile failure frequently occurred in the wellbore, dynamic Brazilian disc splitting tests were carried out. The cumulative damage of the rock increased exponentially with increasing strain rate, the ultimate failure modes of the disc rock samples were closely related to the impact velocity, and the dynamic tensile strengths measured by the test were far larger than the static tensile strengths [ 21 – 24 ]. Analysing the above studies, it was found that high temperature, high in situ stress and dynamic disturbances were taken into account, but the influence of the cross section of high-depth wellbores, medium water and cycle heat recovery times was overlooked.…”
Section: Introductionmentioning
confidence: 99%